Wildfire and topography drive woody plant diversity in a Sky Island mountain range in the Southwest USA - Andrew M. Barton (Wiley, 2021)
Abstract Aim Drastic changes in fire regimes are altering plant communities, inspiring ecologists to better understand the relationship between fire and plant species diversity. We examined the impact of a 90,000‐ha wildfire on woody plant species diversity in an arid mountain range in southern Arizona, USA. We tested recent fire‐diversity hypotheses by addressing the impacts on diversity of fire severity, fire variability, historical fire regimes, and topography. Location Chiricahua National Monument, Chiricahua Mountains, Arizona, USA, part of the Sky Islands of the US–Mexico borderlands. Taxon Woody plant species. Methods We sampled woody plant diversity in 138 plots before (2002–2003) and after (2017–2018) the 2011 Horseshoe Two Fire in three vegetation types and across fire severity and topographic gradients. We calculated gamma, alpha, and beta diversity and examined changes over time in burned versus unburned plots and the shapes of the relationships of diversity with fire severity and topography. Results Alpha species richness declined, and beta and gamma diversity increased in burned but not unburned plots. Fire‐induced enhancement of gamma diversity was confined to low fire severity plots. Alpha diversity did not exhibit a clear continuous relationship with fire severity. Beta diversity was enhanced by variation in fire severity among plots and increased with fire severity up to very high severity, where it declined slightly. Main Conclusions The results reject the intermediate disturbance hypothesis for alpha diversity but weakly support it for gamma diversity. Spatial variation in fire severity promoted variation among plant assemblages, supporting the pyrodiversity hypothesis. Long‐term drought probably amplified fire‐driven diversity changes. Despite the apparent benign impact of the fire on diversity, the replacement of two large conifer species with a suite of drought‐tolerant shrubs signals the potential loss of functional diversity, a pattern that may warrant restoration efforts to retain these important compositional elements.